Intraluminal pyloric duplication cyst- a rare cause of non-bilious vomiting in a neonate: A case report - Ravi Patcharu; Jaiprakash Yadav; Karunesh Chand; Badal Parikh (EL-Med-Pub, 2021)
Background: Duplications of the alimentary tract are rare congenital malformations, out of which, true pyloric duplications constitute only 2.2%. They present with non-bilious vomiting and mimic hypertrophic pyloric stenosis (HPS). Pyloric duplications that are intraluminal are not separately visible at laparotomy, making their diagnosis difficult.  Case presentation: Our case is a neonate with an intraluminal pyloric duplication cyst who presented with recurrent vomiting. The radiological evaluation suggested a duplication cyst medial to the second part of the duodenum towards the stomach's lesser curvature with features of gastric outlet obstruction. Intraoperatively, a cystic mass of 1 x 2 cm intraluminally was found on opening the pylorus which was excised and pyloroplasty was done. Postoperatively the baby was discharged in a stable condition. Conclusion: Intraluminal pyloric duplication cysts are rare and the clinical presentation mimics HPS. They should be considered as a differential diagnosis in a neonate presenting with features of gastric outlet obstruction.